2019
DOI: 10.1177/1533033819827317
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Transcriptome and Prognosis Data Identifies FGF22 as a Prognostic Marker of Lung Adenocarcinoma

Abstract: Lung adenocarcinoma is one of the most common cancers worldwide. However, the molecular mechanisms of lung adenocarcinoma development are still unclear. This study aimed to investigate the expression profiles of anti-lung cancer target genes in different cancer stages and to explore their functions in tumor development. Lung adenocarcinoma transcriptome and clinical data were downloaded from Genomic Data Commons Data Portal, and the anti-lung cancer target genes were retrieved from the Thomson Reuters Integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…623 Huang et al 624 found that overexpression of FGF21 delayed the appearance of diethylnitrosamine-induced liver tumors and proposed that FGF21 might delay development of adenomas through activation of resident hepatocyte FGFR4 at early time. Liu et al 625 demonstrated that FGF22 expression was tightly associated with the poor overall survival. FGF23 is present at an increased level and promotes the progression of prostate cancer.…”
Section: Fgf Signaling In Tumorsmentioning
confidence: 99%
“…623 Huang et al 624 found that overexpression of FGF21 delayed the appearance of diethylnitrosamine-induced liver tumors and proposed that FGF21 might delay development of adenomas through activation of resident hepatocyte FGFR4 at early time. Liu et al 625 demonstrated that FGF22 expression was tightly associated with the poor overall survival. FGF23 is present at an increased level and promotes the progression of prostate cancer.…”
Section: Fgf Signaling In Tumorsmentioning
confidence: 99%
“…The information on human genes and related GO biological functions were downloaded from the QuickGO database ( http://www.ebi.ac.uk/QuickGO-Beta/ ). GO enrichment analysis was performed using a hypergeometric test and the formula shown in a previous report [ 67 ]. An FDR corrected P -value ≤ 0.05 was considered significantly enriched.…”
Section: Methodsmentioning
confidence: 99%
“…All bioinformatics analysis was performed using R version 3.4.1 software ( https://www.r-project.org/ ) and the Bioconductor library ( http://www.bioconductor.org/ ). The detailed methods of differential expression gene analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, co-expression network analysis, and survival analysis were performed, as previously described [14]. Differentially expressed genes were calculated for each stage (I, II, III/IV).…”
Section: Methodsmentioning
confidence: 99%